If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -7(x + 3) = -3(x + 3) Reorder the terms: -7(3 + x) = -3(x + 3) (3 * -7 + x * -7) = -3(x + 3) (-21 + -7x) = -3(x + 3) Reorder the terms: -21 + -7x = -3(3 + x) -21 + -7x = (3 * -3 + x * -3) -21 + -7x = (-9 + -3x) Solving -21 + -7x = -9 + -3x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '3x' to each side of the equation. -21 + -7x + 3x = -9 + -3x + 3x Combine like terms: -7x + 3x = -4x -21 + -4x = -9 + -3x + 3x Combine like terms: -3x + 3x = 0 -21 + -4x = -9 + 0 -21 + -4x = -9 Add '21' to each side of the equation. -21 + 21 + -4x = -9 + 21 Combine like terms: -21 + 21 = 0 0 + -4x = -9 + 21 -4x = -9 + 21 Combine like terms: -9 + 21 = 12 -4x = 12 Divide each side by '-4'. x = -3 Simplifying x = -3
| 5x+10/15 | | 5x+40=9x-12 | | 0.25r+0.25+0.25r=0.5+0.25r | | 3.7x=2.9x+4.8 | | 4x-9=3.5x | | 7(-4x+7)=-7 | | 7=-x+3y | | 1/5=m/30 | | 20(v+4)-4v=4(4v+2)-11 | | 124=4x+-10y | | 2x+x+5-5=6 | | 4(p-6q)=0 | | -20=5(3x-10)-5x | | 118=8(1+7n)-2 | | 1/5x=x | | 8(3-5a)=-296 | | 7x^(2/3)-63=0 | | 3/7b=9 | | 14+c=39 | | 22/25X15/52X8/33 | | 8(3-5a)=-188 | | 5(-3x+5)=6-4x | | 27x-19-39x=-65 | | -3(2x+3)=6x+9 | | -0.1x+1.25=-0.5x+4.45 | | 8-9t=21r-17 | | (6+y)(2y+3)=0 | | 6p-16p=70 | | 3w+2-w=-3 | | 45x-21-17x=-63 | | 84=2k-5(2k-4) | | 3(x-1)+41=x-7(x+1) |